2017
DOI: 10.1002/2016ja023297
|View full text |Cite
|
Sign up to set email alerts
|

On the governing dynamics of the VHF radar echoes from the mesosphere and collision‐dominated lower E region over Gadanki (13.5°N, 79.2°E)

Abstract: In the present communication, the role of neutral dynamical processes in governing the morphology and seasonal variations of daytime VHF radar echoes from the mesosphere and the collision‐dominated lower E region is discussed. While the seasonal variations of mesospheric echo occurrence show semiannual variation with their maxima in the equinoxes, the occurrence of E region echoes shows strong annual variation peaking in the summer with two secondary maxima identical to semiannual variation of the mesospheric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Given that the metallic ions could reduce the incoherent scatter spectral width by about 20% (Tepley & Mathews, 1985), the enhanced echoes with narrow spectral width could be associated with such effect on the NEIS. Further, the fact that the meteor flux maximizes in the local summer in the Indian sector (Selvaraj et al, 2017) and they are likely to be uplifted by the prevailing daytime eastward electric field, it is quite reasonable to consider the presence of metallic ions in the 150‐km altitude region. Also the meteor ablation rate being higher during the solar minimum than in solar maximum (e.g., Campbell‐Brown, 2019) stimulates to consider the role of metallic ions to understand the reason for more occurrence of Type‐B echoes during local summer and low solar activity (Patra & Pavan Chaitanya, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the metallic ions could reduce the incoherent scatter spectral width by about 20% (Tepley & Mathews, 1985), the enhanced echoes with narrow spectral width could be associated with such effect on the NEIS. Further, the fact that the meteor flux maximizes in the local summer in the Indian sector (Selvaraj et al, 2017) and they are likely to be uplifted by the prevailing daytime eastward electric field, it is quite reasonable to consider the presence of metallic ions in the 150‐km altitude region. Also the meteor ablation rate being higher during the solar minimum than in solar maximum (e.g., Campbell‐Brown, 2019) stimulates to consider the role of metallic ions to understand the reason for more occurrence of Type‐B echoes during local summer and low solar activity (Patra & Pavan Chaitanya, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, Gurubaran and Rajaram () observed maximum activity of diurnal tide in June in addition to the semiannual variation and noted its biennial variation. Selvaraj et al () noted shorter vertical wavelength of diurnal tide in mesospheric winds over Tirunelveli (8.7°N, 77.8°E) and attributed it to the nonmigrating tide. The present study shows large enhancement of DE4 during June, when DW1 is minimum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well reported that the convergence of the ions forms the Es through the wind shear driven by the tides and waves (Krall et al, 2020;Axford, 1963;Whitehead, 1961;Mathews, 1998;Haldoupis, 2012;Selvaraj et al, 2017). Based on the descending speed of the Es, USD, and USN layers, dominant control by the semidiurnal and diurnal tides is identified (Christakis et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Layering phenomena have been observed in the lower ionosphere for many decades (Christakis et al, 2009;Mathews, 1998;Whitehead, 1989;Mathews & Bekeny, 1979;Shen et al, 1976;Axford, 1963;Whitehead, 1961;McNicol & Gipps, 1951;Haldoupis, 2012;Earle et al, 2000;Fujitaka & Tohmatsu, 1971, 1973 globally, and in particular at Arecibo using the powerful 430 MHz incoherent scatter radar. Early power profile observations showed the remarkable complexity of so-called sporadic layers, and the development of the wind shear theory, as applied to metallic ions, has also proceeded over several decades (Axford, 1963;Whitehead, 1961;Mathews, 1998;Haldoupis, 2012;Selvaraj et al, 2017). The studies broadened to include somewhat higher altitudes, encompassing so-called intermediate descending layers (IDLs).…”
Section: Introductionmentioning
confidence: 99%